Perancangan Jaringan Virtual Metametarouter - Abdul Rozak; Ahmad Susan Pardiansyah (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
SMK BangunBangsa have computer networking hardware to do the lab network, but the device is a computer network that is owned by SMK Bangun Bangsa are very limited one example, the lack of devices MetaRouterboard, while in the lab network SMK Bangu Bangsa want to simulate a LAN and MAN real simulation but limitations of network devices. So some questions arise: Is simulated LAN and MAN networks can be implemented while the lack of hardware support on vocational Build People? In this study, researchers have conducted the data collection methods and apply methods of analysis, from the results, the researchers have to get a solution to implement the LAN and MAN networks simulating real simulation with "Designing Virtual Networking MetaMetaRouter", using design methods PPDIOO. Implementation of Virtual MetaMetaRouter at SMK Bangun Bangsa, both LAN and MAN networks simulating real simulation can ultimately be applied and save in the procurement of network hardware.